Hydrodynamic Characteristics of an Underwater Manipulator in Pulsating Flow - Liu, Xia; Duan, Derong; Zhang, Xiaoya; Cheng, Yujun; Zhang, Hui (Journal of marine science and application, 2025)
Pulsating flow is a common condition for underwater manipulators in Bohai Bay. This study aimed to investigate the effects of pulsation frequency and amplitude on the hydrodynamic characteristics of an underwater manipulator with different postures using the user-defined function (UDF) method. The lift coefficient ( C L ), drag coefficient ( C D ), and vortex shedding of the underwater manipulator in single- and dualarm forms were obtained. Results indicated that the maximum increase in the lift and drag coefficients subjected to the pulsation parameters was 24.45% and 28%, respectively, when the fluid flowed past a single arm. Compared with the single arm, the lift and drag coefficients of the arms were higher than those of the single arm when arm 2 was located upstream. Additionally, the pulsation frequency had no obvious effect on the manipulator, but the C L and C D of arm 2 showed an obvious increasing trend with an increase in pulsation amplitude. Meanwhile, when arm 2 was located downstream, the C L and C D of arm 2 were reduced by 16.38% and 1.15%, respectively, with an increase in the pulse frequency, and the maximum increase in the lift and drag coefficients was 33.33% and 16.78%, respectively, with increasing pulsation amplitude. Moreover, the downstream wake morphology changed significantly, and a combined vortex phenomenon appeared. Finally, a theoretical basis for examining the hydrodynamic characteristics of marine engineering equipment was established to aid future marine resource exploitation.